Simultaneous Topical Antifungal Skin and Nail Therapy: A Prospective Treatment Option? - Täuber, A.; Müller-Goymann, C. (Aktuelle Dermatologie, 2015)
Superficial fungal infections affect 20 – 25 % of the world’s population with an increasing trend. Common infections are fungal skin and nail diseases (tinea pedis and onychomycosis, respectively), which often occur simultaneously due to autoinoculation. Tinea pedis is mostly provoked by the dermatophyte fungus Trichophyton rubrum, which remains in the outermost skin layer, the stratum corneum (SC). Normally, the treatment is done topically and takes up to four weeks. Just as tinea pedis, about 90 % of onychomycoses is triggered by T. rubrum and Trichophyton mentagrophytes. Toenail onychomycosis is 4 – 10 times more common in comparison to fingernails. The nail plate is 0.25 – 1.0 mm thick and consists of densely packed keratin cell layers. With a water content of up to 25 % and a lipid content of 0.1 – 1 %, the nail plate is considered as a hydrophilic gel membrane with an additional lipophilic route. Due to its excellent barrier properties and a growth rate of only 2 – 3 mm per month, nail mycosis treatment is a remarkable challenge and is often accompanied by high relapse rates. In contrast to the nail plate, SC is considered as an approximately 10 µm thick, predominantly lipophilic barrier. Because of the distinct structure of these tissues, hitherto, there are only formulations marketed for either tinea pedis or onychomycosis. A formulation targeting both would therefore be a considerable improvement, but has to fulfil different characteristics. The following review focuses on potential active pharmaceutical ingredients (API) for simultaneous tinea pedis and onychomycosis treatment as well as in vitro models for antifungal efficacy evaluation. It carves out the challenges in simultaneous therapy based on the distinct structure of nail and SC.